KONTRIBUSI VO2 MAX DAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLING SEPAKBOLA EKSTRAKURIKULER SMK NEGERI KEHUTANAN PEKANBARU - Ariyanto, Dwi; Saripin, Saripin; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the authors' observation when the team conducts trials and official matches, championships between high schools in Pekanbaru city, and competition LPI (Indonesia Education League)many students are lacking in dribbling motion, the ball is often released and easily controlled or taken by the opponent , mastery of the ball at the time of dribbling. The purpose of this study is to know the contribution of VO2 max and Agility With Dribbling Skills Extracurricular Football SMK Negeri Kehutanan Pekanbaru Population in researching all students (son) extracurricular soccer vocal State Forestry of Pekanbaru which amounted to 17 people. The sample in this study is less than one hundred then the sample is taken by (total sampling) or technique of sampling fully student (son) ektrakulikuler SMK Negeri Kehutanan Pekanbaru which amounts 17 people. Based on the results of the research which the author has described in the previous chapter, it can be concluded as follows: There is a relationship between agility with dribbling skills, where rtab at significant level Î± (0.05) = 0.497 means rhitung (0.736)> rtab (0.497 ). With contribution of 54,24% with Medium category. Then there is relationship between endurance (VO2 Max) with dribbling skill, where rtab at significant level Î± (0,05) = 0,497, mean rhitung (0,560)> rtab (0,497) with contribution equal to 31,31% with category less, and there is a relationship between agility and endurance (VO2 Max) with student doling skills Extracurricular SMK Negeri Kehutanan Pekanbaru, where rtab at significant level Î± (0.05) = 0.497, means Rhitung (0.796)> rtab (0.497 ), with contribution of 63,36% with Good category.Keywords: Agility, Endurance, Dribbling Skill